Implementation of ‘Freedom to Learn, Independent Campus’ (MBKM) Policy - Abunawas Tjaija (STAI Hubbulwathan Duri, 2022)
The ‘Freedom to Learn, Independent Campus’ or MBKM program is a flagship program that aims to create competitive, skilled, independent, and innovative students. This study aims to determine the implementation of the MBKM program in the Faculty of Social and Political Sciences one of the universities in Central Sulawesi Province. This study used a quantitative approach. The population was the study program and MBKM units consisting of the faculty, lecturers, and students with a total of 111 respondents. The sampling used a purposive sampling technique to determine the criteria. The number of samples used a census so that the entire population was sampled. Data were collected by observation, questionnaires, and documentation. Then, data were analyzed using descriptive statistics guided by the mean value. The results of the study showed that the implementation of MBKM has not been effective in terms of communication, resources, and the attitude of the implementers, especially in the dimension of resources for the indicators of human resources and supporting facilities which are important to be considered in the implementation of MBKM program. Meanwhile, the dimensions of the bureaucratic structure have been effective as the standard operating procedures have been provided in the form of guidelines or implementation guidebooks. Furthermore, the responsibilities or authorities in implementing policies and the path of coordination have been well distributed.